Evaluating sub-tenon anesthesia in manual small incision cataract surgery: efficacy and safety - Javed, Musawar; Nazullah; Miraj, Khkola (International Journal of Pathology, 2026)
Background: Cataract remains the leading cause of preventable blindness worldwide. While local anesthesia is essential for cataract surgery, traditional techniques like peribulbar and retrobulbar blocks carry significant risks. Sub-Tenon anesthesia has emerged as a potentially safer alternative, though its efficacy rates vary widely in literature, and data from the local population is limited. Our objective is to evaluate the efficacy and safety of Sub-Tenon anesthesia in patients undergoing Manual Small Incision Cataract Surgery (MSICS) at a tertiary care hospital in Peshawar, Pakistan.Methods: This descriptive case series was conducted at the Department of Ophthalmology, Hayatabad Medical Complex. A total of 148 patients undergoing MSICS under Sub-Tenon anesthesia were enrolled using non-probability consecutive sampling. Akinesia was assessed using a standardized scoring system (0-12) ten minutes after anesthetic administration, with complete akinesia (score=0) defined as effective. Secondary outcomes included intraoperative pain (measured using the 10-point Visual Analog Scale (VAS; 0 = no pain, 10 = worst possible pain), surgical duration, and adverse events. Data were analyzed using SPSS version 24 with appropriate statistical tests.Results: The overall efficacy of Sub-Tenon anesthesia was 56.1% (83/148). Patients with effective blocks reported significantly lower pain scores (median VAS: 1.30 vs 3.90, p<0.001) and had shorter surgical duration (median: 26 vs 33 minutes, p<0.001). Multivariate analysis showed that lower pain scores (adjusted OR: 0.11, 95% CI: 0.05-0.21, p<0.001) and shorter surgery duration (adjusted OR: 0.91, 95% CI: 0.82-0.99, p=0.031) were significantly associated with effective anesthesia. The technique demonstrated favorable safety profile with only minor, self-limiting adverse events (overall incidence: 4.1%).Conclusion: Sub-Tenon anesthesia provides moderate efficacy with exceptional safety for MSICS. Successful blocks are associated with significantly improved patient comfort and surgical efficiency. This technique represents a viable alternative to sharp-needle approaches, particularly in settings prioritizing patient safety.